Different types of intranasal steroids for chronic rhinosinusitis - Chong, Lee Yee; Head, Karen; Hopkins, Claire; Philpott, Carl; Burton, Martin J; Schilder, Anne G M (Cochrane database of systematic reviews, 2016)
This review is one of six looking at the primary medical management options for patients with chronic rhinosinusitis.Chronic rhinosinusitis is common and is characterised by inflammation of the lining of the nose and paranasal sinuses leading to nasal blockage, nasal discharge, facial pressure/pain and loss of sense of smell. The condition can occur with or without nasal polyps. Topical (intranasal) corticosteroids are used with the aim of reducing inflammation in the sinonasal mucosa in order to improve patient symptoms. To assess the effects of different types of intranasal steroids in people with chronic rhinosinusitis. The Cochrane ENT Information Specialist searched the ENT Trials Register; Central Register of Controlled Trials (CENTRAL 2015, Issue 7); MEDLINE; EMBASE; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 11 August 2015. Randomised controlled trials (RCTs) with a follow-up period of at least three months comparing first-generation intranasal corticosteroids (e.g. beclomethasone dipropionate, triamcinolone acetonide, flunisolide, budesonide) with second-generation intranasal corticosteroids (e.g. ciclesonide, fluticasone furoate, fluticasone propionate, mometasone furoate, betamethasone sodium phosphate), or sprays versus drops, or low-dose versus high-dose intranasal corticosteroids. We used the standard methodological procedures expected by Cochrane. Our primary outcomes were disease-specific health-related quality of life (HRQL), patient-reported disease severity and the commonest adverse event - epistaxis (nosebleed). Secondary outcomes included general HRQL, endoscopic nasal polyp score, computerised tomography (CT) scan score and the adverse event of local irritation. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. We included nine RCTs (911 participants), including four different comparisons. None of the studies evaluated our first primary outcome measure, disease-specific HRQL. Fluticasone propionate versus beclomethasone dipropionate We identified two small studies (56 participants with polyps) that evaluated disease severity and looked at the primary adverse effect: epistaxis , but no other outcomes. We cannot report any numerical data but the study authors reported no difference between the two steroids. The evidence was of very low quality. Fluticasone propionate versus mometasone furoate We identified only one study (100 participants with polyps) that evaluated disease severity (nasal symptoms scores), which reported no difference (no numerical data available). The evidence was of very low quality. High-dose versus low-dose steroidsWe included five studies (663 participants with nasal polyps), three using mometasone furoate (400 µg versus 200 µg in adults and older children, 200 µg versus 100 µg in younger children) and two using fluticasone propionate drops (800 µg versus 400 µg). We found low quality evidence relating to disease severity and nasal polyps size, with results from the high-dose and low-dose groups being similar. Although all studies reported more improvement in polyp score in the high-dose group, the significance of this is unclear due to the small size of the improvements.The primary adverse effect, epistaxis , was more common when higher doses were used (risk ratio (RR) 2.06, 95% confidence interval (CI) 1.20 to 3.54, 637 participants, moderate quality evidence). Most of the studies that contributed data to this outcome used a broad definition of epistaxis, which ranged from frank bleeding to bloody nasal discharge to flecks of blood in the mucus. Aqueous nasal spray versus aerosol spray We identified only one poorly reported study (unclear number of participants for comparison of interest, 91 between three treatment arms), in which there were significant baseline differences between the participants in the two groups. We were unable to draw meaningful conclusions from the data. We found insufficient evidence to suggest that one type of intranasal steroid is more effective than another in patients with chronic rhinosinusitis, nor that the effectiveness of a spray differs from an aerosol. We identified no studies that compared drops with spray.It is unclear if higher doses result in better symptom improvements (low quality evidence), but there was moderate quality evidence of an increased risk of epistaxis as an adverse effect of treatment when higher doses were used. This included all levels of severity of epistaxis and it is likely that the proportion of events that required patients to discontinue usage is low due to the low numbers of withdrawals attributed to it. If epistaxis is limited to streaks of blood in the mucus it may be tolerated by the patient and it may be safe to continue treatment. However, it may be a factor that affects compliance.There is insufficient evidence to suggest that the different types of corticosteroid molecule or spray versus aerosol have different effects. Lower doses have similar effectiveness but fewer side effects.Clearly more research in this area is needed, with specific attention given to trial design, disease-specific health-related quality of life outcomes and evaluation of longer-term outcomes and adverse effects.